Describing the Access Network by means of Router Buffer Modelling: A New Methodology. (24th July 2014) - Sequeira, Luis; Fernández-Navajas, Julián; Saldana, Jose; Gállego, José Ramón; Canales, María
Abstract : The behaviour of the routers' buffer may affect the quality of service (QoS) of network services under certain conditions, since it may modify some traffic characteristics, as delay or jitter, and may also drop packets. As a consequence, the characterization of the buffer is interesting, especially when multimedia flows are transmitted and even more if they transport information with real-time requirements. This work presents a new methodology with the aim of determining the technical and functional characteristics of real buffers (i.e., behaviour, size, limits, and input and output rate) of a network path. It permits the characterization of intermediate buffers of different devices in a network path across the Internet.